Evaluating the Correlation of Hedgehog Pathway with Claudin-1 Expression in Invasive Breast Cancer: Correlation of Hedgehog Pathway with Claudin-1 Expression - Chen, Daping; Cheng, Xing (Cellular and Molecular Biology, 2023)
Being a heterogeneous disease, breast cancer illustrates different biological and phenotypic features which make its diagnosis and treatment challenging. This study aimed to evaluate the expression levels of crucial components of the Hedgehog signaling pathway, the correlation between the signal transducer Smo, and clinicopathologic features (lymph node metastasis and metastasis stage) in invasive breast carcinoma. Besides, the inverse correlation was considered between expression levels of Smo and Claudin-1. For this purpose, in a case-control study, we evaluated 72 tumor and adjacent normal tissue specimens obtained from invasive ductal breast cancer patients. The expression levels of Hedgehog signaling components (Smo, Gli1, and Ptch), Claudin-1, E-cadherin, and MMP2 were measured by qRT-PCR. The correlations between Smo expressions with some clinicopathologic parameters were also analyzed. Compared to normal adjacent tissues, the results showed up-regulation of Hedgehog signaling in invasive breast carcinoma samples. Upregulation of the signal transducer Smo correlated with tumor stages and lymph node metastasis of the breast tumors. This correlation was affected by the expression of Her2. A significant correlation existed between expression levels of the signal transducer Smo and Claudin-1, E-cadherin as an epithelial cell marker, and MMP2 as a metastasis-related gene in advanced metastatic tumor samples. Based on the obtained results, a new layer of molecular complexity was found, which should be considered in managing patients with invasive breast carcinoma. The results suggested a key role for Hedgehog signaling in invasive breast carcinoma. In terms of the inverse correlation between expression levels of Claudin-1 and Hedgehog signaling, Claudin-1 could serve as a candidate gene in diagnostic studies. Thus, its clinical significance should be further clarified.